Peran Harga, Promosi, dan Kualitas Produk Dalam Mendorong Keputusan Pembelian Kembali di Bale Ayu Denpasar - I Made Yudiana; Ni Luh Putu Indiani (Universitas Warmadewa, 2022)
The wood processing business is one of business fields in Bali with tight level of competition. Bale Ayu, one of the companies engaged in wood processing business, which is the object of this research, has consistently experienced decline in its target achievement every year. This reflects a problem in consumer interest in buying or repurchasing. This becomes the background of this study to analyze the factors that encourage consumer interest to repurchase. This study aims to analyze the influence of price, promotion, and product quality on customer repurchase decision at Bale Ayu. The population in this study is 190 Bale Ayu customers. The data collection method is a survey method with a questionnaire. Multiple linear regression analysis technique was used to test the effect of independent variable on dependent variable. The study results showed that price, promotion, and product quality has a positive and significant effect on repurchase decision. Aspects that need to be considered to improve the quality of pricing policy are: setting competitive and affordable prices, providing discounts, and offering various payment options (cash/debit/credit). Aspects that need to be considered to improve the quality of promotion are: promoting products through advertisements in various media, providing discounts, and publicizing products through various programs such as exhibitions, affiliate marketing, etc. Aspects that need to be considered to improve product quality are: making sure the product functions properly, conformed to the specifications, improving product durability, producing products with attractive designs, and maintaining product quality.